2005
DOI: 10.1016/j.ydbio.2004.11.032
|View full text |Cite
|
Sign up to set email alerts
|

A maternal store of macroH2A is removed from pronuclei prior to onset of somatic macroH2A expression in preimplantation embryos

Abstract: MacroH2A histones are variants of canonical histone H2A that are conserved among vertebrates. Previous studies have implicated macroH2As in epigenetic gene-silencing events including X chromosome inactivation. Here we show that macroH2A is present in developing and mature mouse oocytes. MacroH2A is localized to chromatin of germinal vesicles (GV) in both late growth stage (lg-GV) and fully grown (fg-GV) stage oocytes. In addition, macroH2A is associated with the chromosomes of mature oocytes, and abundant macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 40 publications
8
62
0
Order By: Relevance
“…Regarding heterochromatin localization, our observations (summarized in Fig. 8) confirm previous data obtained mostly through immunostainings (Chang et al, 2005;De La Fuente et al, 2004;Garagna et al, 2004; Longo et respectively) during this transition. This is consistent with the number of centromeric spots previously reported by Garagna and coworkers (2004) in fully matured GV oocytes (about 15 detected with CREST antibodies).…”
Section: Three Dimensional Localization Of Constitutive Heterochromatsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding heterochromatin localization, our observations (summarized in Fig. 8) confirm previous data obtained mostly through immunostainings (Chang et al, 2005;De La Fuente et al, 2004;Garagna et al, 2004; Longo et respectively) during this transition. This is consistent with the number of centromeric spots previously reported by Garagna and coworkers (2004) in fully matured GV oocytes (about 15 detected with CREST antibodies).…”
Section: Three Dimensional Localization Of Constitutive Heterochromatsupporting
confidence: 91%
“…In interphasic somatic cells, these regions are usually forming chromocenters that represent clusters of the pericentric regions of different chromosomes, surrounded by the centromeres of the corresponding chromosomes (Bannister et al, 2001;Lachner et al, 2001). In GV oocytes, it has already been demonstrated that HP1 (a or b) proteins -known to be associated with pericentromeric heterochromatin (Bannister et al, 2001;Lachner et al, 2001)-co-localize with highly condensed areas of chromatin in the nucleoplasm of NSN and SN oocytes as well as around the NLB of SN oocytes (Chang et al, 2005;Liu et al, 2012;Meglicki et al, 2008;Wang et al, 2008). It was also shown that centromeres cluster around the NLB in SN oocytes only (De La Fuente et al, 2004;Garagna et al, 2004;Liu et al, 2012;Longo et al, 2003;Zuccotti et al, 2005), suggesting that pericentromeric heterochromatin distribution is reorganized during the NSN to SN transition.…”
Section: Introductionmentioning
confidence: 99%
“…Embryos were prepared for IF as previously described (Chang et al, 2005;Lin et al, 2010). The following antibodies were used: H3.3 (Abnova H00003021-M01; Abcam ab62642), H3 (Abcam ab1971), H4K16ac (Millipore 07-329), H3K36me2 (Abcam ab9049), H1 (Abcam ab1938; ab62884), H3K4me3 (Millipore 04-745), H3K9me2 (Abcam ab1220), H3K9me3 (Abcam ab8898), H3K27me3 (Millipore 07-449), HP1β (Santa Cruz sc-10212), H4K5/8/12ac (Upstate 04-557), Pan-H4ac (Millipore 06-866), Mof (Santa Cruz Biotechnology sc-13677), Cdx2 (Biogenex Laboratories MU392) and Oct4 (Pou5F1; Santa Cruz Biotechnology sc-9081).…”
Section: Immunofluorescence (If) Imagingmentioning
confidence: 99%
“…Embryos made by somatic nuclear transfer utilize the same chromatin remodeling mechanisms. [62,63] HDAC1 is expressed in preimplantation embryos , where its expression inversely correlates with changes in the acetylation state of histone H4K5 during preimplantation development HDAC1 is involved in the formation of a chromatin-mediated transcriptionally repressive state that initiates in the late two-cell embryo [31] ICC of late zygotes shows that constitutive heterochromatin is only maternally labeled by H3K9me3 and HP1…”
Section: Harvesting Oocytes and Preimplantation Embryosmentioning
confidence: 99%